Healthcare Funding Priority Setting: A Contested Health Policy Issue - Shiri, Simon (Prabandhan: Indian Journal of Management, 2015)
This paper critically reviewed interdisciplinary literatures on a topical issue of priority setting in health care funding and proposed an Integrated Health Care Policy Scoping Framework and a corresponding Integrated Healthcare Funding Model, which is consistently applicable across global health care organizations to generate further debate on the subject. There is an existing unique gap in terms of a universally acceptable framework for allocating health care funding resources that is applicable to National Health Care Systems, which provides managers with health care resources to achieve sustainable profitability in both private and public healthcare organizations. Based on an international business perspective of healthcare both as a public good and a commercial entity, the topical debate appraised the close relationships that exist among the benchmarking variables of health policy and health care marketing in proximity to internal and external systems; social-political-economic factors and organizational strategy; as a way of demonstrating an open venture inventiveness to maximize sustainable organizational value at a competitive cost leadership and product differentiation advantage to both existing and new competitors.